2017
DOI: 10.1002/adfm.201705069
|View full text |Cite
|
Sign up to set email alerts
|

Hofmeister Effect‐Assisted One Step Fabrication of Ductile and Strong Gelatin Hydrogels

Abstract: Hydrogels with high strength and ductility are normally prepared from synthetic polymers, and most protein-based hydrogels are soft and brittle. Here, a strong, ductile gelatin hydrogel is prepared by simply soaking a virgin gelatin gel in an ammonium sulfate solution. The polymer chains in the covalent, crosslink-free network can freely move to homogeneously distribute stress, and more importantly, the highly kosmotropic ammonium sulfate ions greatly enhance the hydrophobic interactions and chain bundling wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
286
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(295 citation statements)
references
References 42 publications
9
286
0
Order By: Relevance
“…Gelatin, derived from collagen, is considered a suitable base component of potential bone replacement materials with a 3D structure . Recently, Wang et al prepared a tough gelatin hydrogel with extraordinary ultimate strength; whereas, the gelatin hydrogel degraded quickly, as ions (CO 3 2− , Cl − , I − ) could render the gel soft and melted within 1 h. Neither slowly nor quickly degrading materials may be suitable for biomedical applications in tissue reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Gelatin, derived from collagen, is considered a suitable base component of potential bone replacement materials with a 3D structure . Recently, Wang et al prepared a tough gelatin hydrogel with extraordinary ultimate strength; whereas, the gelatin hydrogel degraded quickly, as ions (CO 3 2− , Cl − , I − ) could render the gel soft and melted within 1 h. Neither slowly nor quickly degrading materials may be suitable for biomedical applications in tissue reconstruction.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] Gelatin is a denatured form of the protein collagen which can be used for tissue repair and controlling drug delivery systems. [18][19][20][21][22] Furthermore, gelatin shows no antigenity and is completely resorbable in vivo. [23] In order to further enhance or modify the performance of gelatin hydrogels, especially the mechanical properties, methacrylic anhydride (MA) was used to modify gelatin.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the increased intensity of the CO stretching vibrations (1670 cm −1 ) suggests the enhanced chain bundling. [28] All evidences confirmed the Hofmeister effect on PVA molecules within hydrogel.…”
mentioning
confidence: 60%
“…Wang et al reported a tough and ductile gelatin hydrogel by immersing the prepared gelatin gel into an ammonium sulfate solution, this treated hydrogel has an extraordinary ultimate strength of 12 MPa based on Hofmeister effect. [28] Similarly, Kouwer et al tuned both the thermoresponsive behavior and mechanical properties of polyisocyanides hydrogel by utilizing the Hofmeister series. [29] While these studies have nothing to do with electrochemical energy storage devices, they provide us abundant experience to design tough hydrogel electrolyte for reliable devices.…”
mentioning
confidence: 99%